PERAN KEPALA SEKOLAH DALAM PENINGKATAN PROFESIONALISME GURU DI SMP NEGERI 1 MOJOWARNO JOMBANG - Afdahlia A. Mansur; Dita Dzata Mirrota (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
The principal is a leader who is mandated by Allah SWT to carry out his duties as a principal in an educational institution and is responsible for all the quality of existing human resources. Because the principal is the first person who is responsible for achieving educational goals. Teacher professionalism is someone who has special abilities and expertise in the field of teacher training so that he is able to carry out his duties with the ability of a professional teacher. The purpose of this study was to describe (1) the role of the principal in increasing teacher professionalism at SMP Negeri 1 Mojowarno Jombang. (2) Professionalism of PAI teachers at SMP Negeri 1 Mojowarno Jombang. This research is field research (field research) which is qualitative in nature, the research form is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results of the study found that the role of the head in increasing teacher professionalism was that the principal always provided motivation for any problems teachers faced at SMP Negeri 1 Mojowarno Jombang, while the professionalism of teachers at SMP Negeri 1 Mojowarno Jombang was that teachers were able to master the material/subject matter to be taught, able to managing teaching and learning programs, being able to use media or learning resources, being able to assess student achievement, and being able to recognize the functions and programs of guidance and counseling